Cultural adaptation of the Cardiff Acne Disability Index to a hindi speaking population: A pilot study - Aayush Gupta; Yugal K Sharma; K Dash; Sampurna Verma (Wolters Kluwer Medknow Publications, 2015)
Background: Acne vulgaris is known to impair many aspects of the quality of life (QoL) of its patients. Aim: To translate the Cardiff Acne Disability Index (CADI) from English into Hindi and to assess its validity and reliability in Hindi speaking patients with acne from India. Methods: Hindi version of CADI, translated and linguistically validated as per published international guidelines, along with a previously translated Hindi version of dermatology life quality index (DLQI) and a demographic questionnaire were administered to acne patients. The internal consistency reliability of the Hindi version of CADI and its concurrent validity were assessed by Cronbach's alpha co-efficient and Spearman's correlation co-efficient respectively. Construct validity was examined by factor analysis. Statistical analysis was carried out using the Statistical Package for the Social Sciences (SPSS) version 20 (SPSS Inc., Chicago, IL, USA) for Windows. Results: One hundred Hindi speaking patients with various grades of acne participated in the study. Hindi version of CADI showed high internal consistency reliability (Cronbach's alpha co-efficient = 0.722). Mean item-to-total correlation co-efficient ranged from 0.502 to 0.760. Concurrent validity of the scale was supported by a significant correlation with the Hindi DLQI. Factor analysis revealed the presence of two dimensions underlying the factor structure of the scale. Conclusion: Hindi CADI is equivalent to the original English version and constitutes a reliable and valid tool for clinical assessment of the impact of acne on QoL.